Gradient nanostructure high-entropy alloy and preparation method thereof

By adopting gradient nanostructured high-entropy alloys composed of iron, manganese, aluminum, nickel and copper elements with specific atomic ratios, and through arc smelting and electromagnetic stirring technology, the existing high-entropy alloys have been solved, and the problems of high cost and poor performance are achieved. High-entropy alloy materials with lower cost and higher performance.

CN119320902APending Publication Date: 2025-01-17CHONGQING IND POLYTECHNIC COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411443267.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing high-entropy alloys contain expensive transition metal elements, which lead to high costs and poor performance, making it difficult to promote in engineering applications.

Method used

The gradient nanostructured high-entropy alloy consisting of iron, manganese, aluminum, nickel and copper elements according to specific atomic ratio was prepared by arc smelting method in an oxygen-free inert gas environment. The Wu electrode was used for multiple melting and electromagnetic stirring. Form the BCC matrix +B2 and L21 nanoparticle structure.

Benefits of technology

It significantly reduces the cost of high-entropy alloy, improves its hardness and strength, has a lower density, and is only 196 yuan/kg, with a hardness of 549HV, and a yield strength of 1106Mpa at room temperature, with a uniform strain of 16.4%, and has achieved Dual optimization of density and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320902A_ABST
    Figure CN119320902A_ABST
Patent Text Reader

Abstract

The invention discloses a gradient nanostructure high-entropy alloy and a preparation method thereof, and belongs to the technical field of alloy preparation, the high-entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper according to the atomic ratio of 32-36: 28-32: 14-16: 7-9: 7-9: 4.5-5.5; the high-entropy alloy is excellent in performance, the price of the high-entropy alloy is lower than that of other high-entropy alloys in the market, and the problems that an existing high-entropy alloy is high in cost and poor in performance can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy preparation, and particularly relates to a gradient nanostructured high entropy alloy and a preparation method thereof. Background Art

[0002] High entropy alloys are often composed of four or more metal elements. High entropy alloys break the conventional design concept and have excellent physical, chemical and mechanical properties, and have attracted global attention and research. However, most of the elements that make up high entropy alloys belong to transition metals, such as strategic elements Co and V, which are expensive, resulting in high alloy costs and difficult to promote in engineering applications. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the present invention provides a gradient nanostructured high entropy alloy and a preparation method thereof. The high entropy alloy has excellent performance and is priced lower than other high entropy alloys on the market, which can effectively solve the problems of high cost and poor performance of existing high entropy alloys.

[0004] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0005] A gradient nanostructured high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in the atomic percentage of 32-36:28-32:14-16:7-9:7-9:4.5-5.5.

[0006] Furthermore, the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 34:30:15:8:8:5.

[0007] Furthermore, the high entropy alloy has a body-centered cubic structure.

[0008] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0009] (1) Calculate the mass ratio of each metal raw material according to the atomic ratio and prepare the ingredients;

[0010] (2) The raw materials are placed in a smelting device and arc-smelted multiple times in an oxygen-free, inert gas environment to obtain the product.

[0011] Furthermore, the purity of each metal raw material in step (1) is greater than 99.95%.

[0012] Furthermore, in step (2), Wu electrodes are used for arc melting.

[0013] Furthermore, the current during smelting in step (2) is 450-550A, and each smelting time is 5-6 minutes.

[0014] Furthermore, the smelting times in step (2) is 4 times, and after each smelting and cooling, the mixture is turned over for the next smelting.

[0015] Furthermore, electromagnetic stirring is performed during the second and third smelting in step (2).

[0016] The beneficial effects produced by the present invention are:

[0017] 1. According to the current market price, the raw material cost of the high entropy alloy block in the present invention is 196 yuan / kg, while the cost of the existing aluminum, cobalt, chromium, iron, manganese and nickel alloys is 324 yuan / kg. The cost of the high entropy alloy of the present invention is reduced by 65%.

[0018] 2. The density of the high entropy alloy in the present invention is 6.8 kg / m3, while the density of the existing aluminum, cobalt, chromium, iron, manganese and nickel alloys is 6.9 kg / m3. The density of the high entropy alloy in the present invention is lower.

[0019] 3. The existing aluminum, cobalt, chromium, iron, manganese, and nickel alloys are BCC matrix + B2 nanoparticles, while the high entropy alloy in the present invention is BCC matrix + B2 nanoparticles + L21 nanoparticles, which is a gradient nanostructured material. The aluminum element promotes the high entropy alloy to form a BCC matrix structure, which can improve the strength and performance of the matrix structure; the copper element is the key to forming L21 nanoparticles and the key to maintaining the cubic form of B2 nanoparticles, which is used to improve the hardness and strength of the alloy, so that the hardness of the high entropy alloy in the present invention can reach about 549HV, while the hardness of the existing high entropy alloy is about 538HV, and the hardness of the high entropy alloy in the present invention is higher. The amount of aluminum and copper elements in the present invention is more critical, and too small or too large an amount cannot achieve a good effect.

[0020] Specifically: the atomic radius of aluminum in the high entropy alloy of the present invention is larger than that of iron, and a body-centered cubic structure is easily formed in the high entropy alloy. However, the aluminum content cannot be too large. Too much aluminum content will lead to increased brittleness of the high entropy alloy. Nickel and aluminum have higher mixing enthalpy, and are easy to form B2 nanophase in the high entropy alloy, which is beneficial to the improvement of alloy strength. Copper can promote the nucleation of B2 phase in the alloy, thereby increasing the volume fraction of B2 phase, but copper is easy to be enriched at the grain boundary, resulting in uneven alloy composition. Therefore, it is necessary to control the content of copper. The high entropy alloy prepared by the ratio of the present invention has a microhardness of up to 549HV, a yield strength of up to 1106Mpa at room temperature, a uniform strain of 16.4%, and a low density of the high entropy alloy of the present invention, which is only 6.8g / cm 3 The cost per kilogram is only 196 yuan, which is a low price and can effectively reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is Fe in Example 1 34 Mn 30 Al 15 SEM photo of Ni8Cr8Cu5 high entropy alloy block, where: Figure 1 a is a SEM photo under low magnification. Figure 1 b is a SEM photo under high magnification;

[0022] Figure 2 is Fe in Example 1 34 Mn 30 Al 15 TEM image of Ni8Cr8Cu5 high entropy alloy block, where: Figure 2 a is the TEM bright field phase, Figure 2 b is Figure 2 Diffraction pattern of area a; Figure 2 c is the L21 phase Dark field phase of crystal surface; Figure 2 d is the B2 phase Acquire dark-field phase of crystal surface;

[0023] Figure 3 is Fe in Example 1 34 Mn 30 Al 15 Transmission electron microscopy scanning results of Ni8Cr8Cu5 high entropy alloy;

[0024] Figure 4 Fe in Comparative Example 1 36 Mn 32 Al 15 Ni 8.5 Cr 8.5 SEM photo of high entropy alloy block, where Figure 4 a is a SEM photo under low magnification. Figure 4 b is a SEM photo under high magnification;

[0025] Figure 5 Fe in Comparative Example 1 36 Mn 32 Al 15 Ni 8.5 Cr 8.5 TEM image of a high entropy alloy block, where: Figure 5 a is the microstructure morphology of the alloy, Figure 5 b is Figure 5 a diffraction pattern; the matrix is ​​a disordered BCC solid solution, and a large number of cubic B2 phase particles are evenly distributed in the matrix;

[0026] Figure 6 Fe in Comparative Example 2 33 Mn 29 Al15 SEM photo of Ni8Cr8Cu7 high entropy alloy block, where Figure 6 a is a SEM photo under low magnification. Figure 6 b is a SEM photo under high magnification;

[0027] Figure 7 Fe in Comparative Example 2 33 Mn 29 Al 15 TEM image of Ni8Cr8Cu7 high entropy alloy block, where: Figure 7 a is the microstructure morphology of the alloy, Figure 7 b is Figure 7 a’s diffraction pattern; Figure 7 c is the L21 phase Dark field photo of crystal surface; Figure 7 d is the B2 phase Obtain dark-field phase photographs of the crystal surface;

[0028] Figure 8 Compression curves of high entropy alloys in Example 1 and Comparative Examples 1-2;

[0029] Fig. 9 This is a macroscopic morphology photograph of the high entropy alloy in Comparative Example 3. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0031] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0032] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0033] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0034] Example 1

[0035] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic percentage of 34:30:15:8:8:5.

[0036] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0037] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0038] (2) placing the raw materials in a smelting device, arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment, with a smelting current of 530 A and a smelting time of 5 min each time. Electromagnetic stirring is performed during the second and third smeltings, and the raw materials are turned over after cooling each time for the next smelting to obtain the product.

[0039] Example 2

[0040] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 35:32:14:7:7:5.

[0041] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0042] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0043] (2) placing the raw materials in a smelting device, and arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment. The current during the melting is 450 A, and the melting time for each time is 5 minutes. Electromagnetic stirring is performed during the second and third meltings. After each melting is cooled, the raw materials are turned over for the next melting to obtain the product.

[0044] Example 3

[0045] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 34:28.5:16:8:8:5.5.

[0046] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0047] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0048] (2) The raw materials are placed in a smelting device, and arc smelting is performed 4 times using a Wu electrode in an oxygen-free, inert gas environment. The current during smelting is 550 A, and each smelting time is 6 minutes. Electromagnetic stirring is performed during the second and third smeltings. After each smelting is cooled, the raw materials are turned over for the next smelting to obtain the product.

[0049] Example 4

[0050] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 33.5:30:16:8:8:4.5.

[0051] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0052] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0053] (2) placing the raw materials in a smelting device, arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment, with a smelting current of 480 A and a smelting time of 6 min each time. Electromagnetic stirring is performed during the second and third smeltings, and the raw materials are turned over after cooling each time for the next smelting to obtain the product.

[0054] Example 5

[0055] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 36:29:15.5:7:7:5.5.

[0056] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0057] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0058] (2) placing the raw materials in a smelting device, arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment, with a smelting current of 520 A and a smelting time of 5 min each time. Electromagnetic stirring is performed during the second and third smeltings, and the raw materials are turned over after cooling each time for the next smelting to obtain the product.

[0059] Comparative Example 1

[0060] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel and chromium elements in an atomic ratio of 36:32:15:8.5:8.5.

[0061] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0062] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0063] (2) placing the raw materials in a smelting device, arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment, with a smelting current of 530 A and a smelting time of 5 min each time. Electromagnetic stirring is performed during the second and third smeltings, and the raw materials are turned over after cooling each time for the next smelting to obtain the product.

[0064] Comparative Example 2

[0065] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic percentage of 33:29:15:8:8:7.

[0066] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0067] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0068] (2) placing the raw materials in a smelting device, arc melting them 4 times using a Wu electrode in an oxygen-free, inert gas environment, with a smelting current of 530 A and a smelting time of 5 min each time. Electromagnetic stirring is performed during the second and third smeltings, and the raw materials are turned over after cooling each time for the next smelting to obtain the product.

[0069] Comparative Example 3

[0070] A gradient nanostructured high entropy alloy, wherein the high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic ratio of 34:30:15:8:8:5.

[0071] The preparation method of the above-mentioned gradient nanostructured high entropy alloy comprises the following steps:

[0072] (1) Calculating the mass ratio of each metal raw material according to the atomic ratio and preparing the ingredients, wherein the purity of each metal raw material is greater than 99.95%;

[0073] (2) The raw materials are placed in a smelting device, and arc smelting is performed once using a Wu electrode in an oxygen-free, inert gas environment. The current during smelting is 550 A, and the smelting time is 6 min.

[0074] Test example

[0075] Taking the high entropy alloys prepared in Example 1 and Comparative Examples 1-2 as examples, their microstructures were observed. The specific results are shown in Figure 1-2 .

[0076] Figure 1 is Fe in Example 1 34 Mn 30 Al 15 SEM photo of Ni8Cr8Cu5 high entropy alloy block, where: Figure 1 a is a SEM photo under low magnification. Figure 1 b is a SEM photograph under a high-power microscope. The results show that the high-entropy alloy has an equiaxed crystal structure with a large number of second phase particles dispersed on the matrix.

[0077] Figure 2 is Fe in Example 1 34 Mn 30 Al 15 TEM image of Ni8Cr8Cu5 high entropy alloy block, where: Figure 2 a is a TEM bright field phase. The results show that a large number of cubic second phase particles with a size of 100-150nm can be clearly seen to be evenly distributed in the matrix. In addition, smaller particles are evenly distributed inside the cubic particles, forming a high entropy alloy with a gradient structure.

[0078] Figure 2 b is the diffraction pattern at the corresponding position. In the figure, three sets of diffraction patterns can be seen. The matrix is ​​a BCC structure, and the other two phases are coherent B2 phase and L21 phase. Crystal plane and B2 phase Dark field acquisition Figure 2c and 2d, it can be seen that the B2 phase is a cubic particle, and the L21 phase is distributed inside the B2 phase and is a small irregular particle. The high entropy alloy was selected for TEM surface scanning, and the results are as follows Figure 3 As shown, it can be seen that the BCC matrix is ​​rich in Fe, Mn, and Cr, the nanoparticles are rich in Al, Ni, and Cu, and the distribution of Cu element on L21 particles is higher than that on B2 phase particles.

[0079] Figure 3 is Fe in Example 1 34 Mn 30 Al 15 Transmission electron microscopy scanning results of Ni8Cr8Cu5 high entropy alloy;

[0080] Figure 4 Fe in Comparative Example 1 36 Mn 32 Al 15 Ni 8.5 Cr 8.5 SEM photo of high entropy alloy block, where Figure 4 a is a SEM photo under low magnification. Figure 4 b is a SEM photo under a high-power microscope; the results show that the alloy has an equiaxed crystal structure, the matrix is ​​a BCC phase, there are coarse grain boundaries, and the grain boundaries are FCC phases;

[0081] Figure 5 Fe in Comparative Example 1 36 Mn 32 Al 15 Ni 8.5 Cr 8.5 TEM image of a high entropy alloy block, where: Figure 5 a is the microstructure morphology of the alloy, Figure 5 b is Figure 5 a diffraction pattern; the matrix is ​​a disordered BCC solid solution, and the results show that a large number of cubic B2 phase particles are evenly distributed in the matrix; compared with Example 1, no finer L21 phase nanoparticles are found;

[0082] Figure 6 Fe in Comparative Example 2 33 Mn 29 Al 15 SEM photo of Ni8Cr8Cu7 high entropy alloy block, where Figure 6 a is a SEM photo under low magnification. Figure 6 b is a SEM photo taken under a high-power microscope; the results show that the alloy is an equiaxed crystal structure, and a large number of nanoparticles are observed in the matrix;

[0083] Figure 7 Fe in Comparative Example 2 33 Mn 29 Al15 TEM image of Ni8Cr8Cu7 high entropy alloy block, where: Figure 7 a is the microstructure morphology of the alloy, Figure 7 b is Figure 7 a’s diffraction pattern; Figure 7 c is the L21 phase Dark field photo of crystal surface; Figure 7 d is the B2 phase The dark field phase photograph was obtained on the crystal surface; the results showed that the high entropy alloy matrix was a disordered BCC solid solution, with a large number of rod-shaped B2 phase particles and L21 phase nanoparticles evenly distributed in the matrix, and the L21 phase particles existed in the B2 phase particle region. Compared with Example 1, the morphology of the B2 phase particles was different;

[0084] Figure 8 Compression curves of the high entropy alloys in Example 1 and Comparative Examples 1-2 show that the compressive yield strength of the high entropy alloy in Example 1 is 1106 MPa, the compressive strength is 1580 MPa, the corresponding uniform strain is 16.4%, and the microhardness of the alloy obtained by testing with a microhardness tester is 549±21 HV.

[0085] Fig. 9 This is a macroscopic morphology photograph of the high entropy alloy in Comparative Example 3. It can be seen that the metal particles are not fully dissolved and an incompletely bonded interface is observed in the ingot.

Claims

1. A gradient nanostructured high entropy alloy, characterized in that: The high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic percentage of 32-36:28-32:14-16:7-9:7-9:4.5-5.

5.

2. The gradient nanostructured high entropy alloy according to claim 1, characterized in that: The high entropy alloy is composed of iron, manganese, aluminum, nickel, chromium and copper elements in an atomic percentage of 34:30:15:8:8:

5.

3. The gradient nanostructured high entropy alloy according to claim 1 or 2, characterized in that: The high entropy alloy has a body-centered cubic structure.

4. The method for preparing the gradient nanostructured high entropy alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Calculate the mass ratio of each metal raw material according to the atomic ratio and prepare the ingredients; (2) The raw materials are placed in a smelting device and arc-smelted multiple times in an oxygen-free, inert gas environment to obtain the product.

5. The method for preparing the gradient nanostructured high entropy alloy as claimed in claim 4, characterized in that: The purity of each metal raw material in step (1) is greater than 99.95%.

6. The method for preparing a gradient nanostructured high entropy alloy as claimed in claim 4, characterized in that: In step (2), arc melting is performed using Wu electrodes.

7. The method for preparing a gradient nanostructured high entropy alloy as claimed in claim 4, characterized in that: The current during smelting in step (2) is 450-550A, and each smelting time is 5-6 minutes.

8. The method for preparing a gradient nanostructured high entropy alloy as claimed in claim 4, characterized in that: The number of smelting in step (2) is 4 times, and the steel is turned over after cooling each time for the next smelting.

9. The method for preparing a gradient nanostructured high entropy alloy as claimed in claim 8, characterized in that: In step (2), electromagnetic stirring is performed during the second and third melting.